The Effects of Selected Brominated and Chlorinated Chemicals on Pseudomonas fluorescens Planktonic Cells and Flow‐Generated Biofilms. Issue 2 (3rd November 2015) - Malheiro, J.; Araújo, P.; Machado, I.; Lemos, M.; Mergulhão, F.; Melo, L.; Simões, M.
Abstract: Sodium hypochlorite (SH) is a widely used disinfectant. However, due to public health and environmental concerns, alternative disinfectants are required. In this study, the control of P seudomonas fluorescens planktonic and biofilm cells was assessed with cetyltrimethylammonium bromide (CTAB), SH, 3‐bromopropionyl chloride (BPC) and 3‐bromopropionic acid (BPA). Their effects were tested against planktonic cells in terms of antimicrobial efficiency and changes on cell surface. CTAB had the lowest minimum inhibitory concentration or minimum bactericidal concentration (20/50 μg/mL). All chemicals promoted cellular disruption and leakage of intracellular constituents. CTAB, BPC and BPA irreversibly changed surface hydrophobicity and charge. Their action was also assessed in the control of flow‐generated biofilms. Modest killing and removal was achieved (maximum killing of 1 log and 16% of total biofilm removal) due to the characteristics of the biofilm. In general, both BPC and CTAB had antimicrobial activities similar to SH and therefore demonstrated potential as alternatives to SH in P . fluorescens control. Practical Applications: The potential environmental and health problems caused by the uncontrolled use of sodium hypochlorite (SH) have led to the search for alternatives, maintaining the antimicrobial efficacy. In fact, SH is included in the indicative list of the Directive on Industrial Emissions (2010/75/EU) as a major pollutant for water emissions and on the formation of carcinogenic and mutagenic products in the presence of organic matter. Therefore, in this study, the antimicrobial potential of selected halogen‐based products was assessed in order to compare their efficacy with SH in the control of planktonic and biofilm cells. All products caused apparent membrane pore formation as well as hydrophobicity and surface charge modification against planktonic cells. Additionally, 3‐bromopropionyl chloride and cetyltrimethylammonium bromide demonstrated similar action to SH in the control of biofilms mimicking an industrial scenario.